Photovoltaic and Impedance Spectroscopy of CdS Quantum Dots Onto Nano Urchin TiO2 Structure for Quantum Dots Sensitized Solar Cell Applications - Ali, Syed Mansoor; Aslam, M.; Farooq, W. A.; Fatehmulla, Amanullah; Atif, M.; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2016)
Quantum dot sensitized solar cell composed on TiO2 nano urchins (TNU) structure on transparent conductive fluorine doped tin oxide glass substrate is fabricated. The impedance spectroscopy properties of the solar cell were investigated. The capacitance voltage, the conductance voltage, the series resistances-voltage characteristics of the solar cell were measured at different frequencies for QDSSC applications. The capacitance voltage measurement shows a trend from the positive to negative capacitance due to injection of electrons from the FTO electrode into TiO2 nanostructure. It is evaluated that the photovoltaic performance of the sensitized solar cell can be improved by the deposition of CdS quantum dots.
Keywords: Impedance Spectroscopy; TiO2 Nano Urchins; Photovoltaic; QDSSC; SILLAR